Value Chains for Nutrition and Smallholder Income - Torero, Máximo (2013)
"Partnering for Impact: IFPRI-European Research Collaboration for Improved Food and Nutrition Security" presentation by Maximo Torero, IFPRI, 25 November 2013 in Brussels, Belgium.